SET-THEORETIC MODELS AND UNIFIED METHODS OF INFORMATION RESOURCES PROCESSING IN E-BUSINESS SYSTEMS - Victoria VYSOTSKA; Lyubomyr CHYRUN (Applied Computer Science, 2014)
In the given article is functional logistic model of commercial content processing as the content life cycle stage in electronic commerce systems proposed. The model of commercial content processing describes the information resources forming in electronic content commerce systems and automation technology simplifies the commercial content mana-gement. In the given article the main problems of electronic content commerce and functional services of commercial content processing are analyzed. The proposed model gives an opportunity to create an instru-ment of information resources processing in electronic commerce systems and to implement the subsystem of commercial content formation, management and support.